2021
DOI: 10.1002/jctb.6729
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of global and Latin‐American trends in nanotoxicology with a focus on carbon nanomaterials: a scientometric approach

Abstract: BACKGROUND:The scientific trends and developments in the field of nanotoxicology were analyzed through a scientometric approach. This study aimed to describe and unravel the main topics on nanomaterials concerning their potential toxicity. It was generated four databases: two for global nanotoxicological papers (Ds1 and Ds2) and two with a Latin-American focus (LA1 and LA2). Ds2 and LA2 databases were constructed with studies dealing with the toxic effects of carbon nanomaterials. Scientometric analyses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Geracitano et al carried out a survey on a large number of published literatures on toxicity of nanomaterials. 2 It was found that most of the literature was focused on one particular nanomaterial, Ag nanoparticles, which have shown good antimicrobial activities. For carbon nanomaterials, a major class of nanomaterials, toxicity research activities are mostly directed towards graphene.…”
Section: In Focus: Latest Development Of Nanotechnology In Latin Americamentioning
confidence: 99%
“…Geracitano et al carried out a survey on a large number of published literatures on toxicity of nanomaterials. 2 It was found that most of the literature was focused on one particular nanomaterial, Ag nanoparticles, which have shown good antimicrobial activities. For carbon nanomaterials, a major class of nanomaterials, toxicity research activities are mostly directed towards graphene.…”
Section: In Focus: Latest Development Of Nanotechnology In Latin Americamentioning
confidence: 99%